2020
DOI: 10.1097/pec.0000000000002148
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diagnosed Concussions in Children Aged 0 to 4 Years Presenting to a Large Pediatric Healthcare Network

Abstract: The aim of the study was to comprehensively describe the natural history of concussion in early childhood between 0 and 4 years.Methods: Retrospective cohort study of 329 patients aged 0 to 4 years, with an International Classification of Diseases, Ninth Revision, concussion diagnosis in the Children's Hospital of Philadelphia healthcare network from October 1, 2013, to September 30, 2015. Clinical data were abstracted from the Children's Hospital of Philadelphia electronic health record, which captured all cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 34 publications
5
16
1
Order By: Relevance
“…These results differ somewhat from previous work documenting greater sleep and irritability symptoms in children 2 years of age and older than in those younger than 2 years. 14,19 The current results do align with these previous studies highlighting the need to include behavioral manifestations when documenting early childhood PCS.…”
Section: Pcs After Early Childhood Mtbisupporting
confidence: 89%
See 2 more Smart Citations
“…These results differ somewhat from previous work documenting greater sleep and irritability symptoms in children 2 years of age and older than in those younger than 2 years. 14,19 The current results do align with these previous studies highlighting the need to include behavioral manifestations when documenting early childhood PCS.…”
Section: Pcs After Early Childhood Mtbisupporting
confidence: 89%
“…Similarly, another study 19 found that although conventional PCS such as headache, irritability, and drowsiness were frequently endorsed by parents of young children, they also reported additional observations such as decreased engagement, behavioral dysregulation, and increased dependence (eg, wanting to be cuddled more). Finally, behavioral changes (eg, increased crying and meltdowns) 14 have been observed in children 2 years of age and younger, reinforcing the idea that existing PCS measures do not adequately capture these unique manifestations.…”
Section: E103mentioning
confidence: 74%
See 1 more Smart Citation
“…20,21 In addition, as most concussion symptom scales have only been validated in children aged five and older, young children may be misdiagnosed with other non-concussion diagnostic codes. 22 Furthermore, previous studies often fail to group visits to distinguish a new injury from a follow-up visit and thereby define EOC. [12][13][14][15] This precludes accurate incidence estimates, which may hamper the efficient allocation of resources.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 In addition, as most concussion symptom scales have only been validated in children aged five and older, young children may be misdiagnosed with other non-concussion diagnostic codes. 22 …”
Section: Introductionmentioning
confidence: 99%